PENJELASAN POLA VOLUME PERDAGANGAN TRADER DENGAN DATA TRANSAKSI ORDER SAHAM DI BURSA EFEK INDONESIA - Ghazali Syamni; Aiyub ,; Juilimursyida Ganto; Azhar , (Media Riset Akuntansi, Auditing & Informasi, 2009)
The objectives of this research is to explain pattern of behavior of trading volume intraday investor inform and investor uninformed, and analysis contribution of the both investors in explaining pattern behavior of investors trading volume in Indonesia Stock Exchange. Regression analysis result indicates that investor or trader informed is more contributionly in explaining trading volume pattern in all time intervals, but not all investors or traders uninformed contributions in all time intervals. Only order informed is more can explain trading volume pattern compared with order uninformed. Regression result finds that order status match have to share is determine trading volume pattern intraday. The role of more determined by INFBM and INFSM compared with UNFBM and UNFSM. While order status amend, open and withdraw is less have casting for determining trading volume pattern intraday. Some possibility of this development of researchs in the future, between the are test the relation of behavior of investors at trading volumes by dividing investor inform with block tradings. This division anticipated to give different response at trading volume pattern. usage of stock transaction data intraday before applying ofpre-opening in Indonesia Stock Exchange.Keywords: trading volume, investor behavior,